THE UTILISATION OF OPPORTUNITIES AND THE OVERCOMING OF OBSTACLES IN THE USE OF TECHNOLOGY IN HADITH STUDIES - Putri, Novi Annisa; Harahap, Shoibatul Aslamiyah; Harahap, Efridawati; Daulae, Tatta Herawati; Nasution, Abdul Riswan (Jurnal Studi Hadis Nusantara, 2024)
The ease with which fraudulent hadiths or hadiths with incorrect interpretations and points of view might emerge is one of the main challenges that technology has brought to the study of hadith. The purpose of this article is to examine the difficulties that come with using hadith in the digital age and to provide technologically based techniques for hadith comprehension and dissemination. The outcomes of this conversation, which was conducted using a descriptive-qualitative method, demonstrate the difficulties in studying hadith in the digital age, including the ease with which fake hadiths proliferate and inflict harm. As a result, employing technology to research hadith necessitates ethical behavior and smart use of already-existing technology. Hadith researchers can use technology responsibly and profitably by upholding religious principles, preserving credibility, safeguarding privacy, and adhering to relevant ethical standards. When used properly, technology can enhance the comprehension, investigation, and sharing of the rich hadith legacy among Muslims worldwide.